Relacje między wartościami społecznymi i ekonomicznymi w ujęciu socjologicznej koncepcji Floriana Znanieckiego - Sajdera, Jolanta (Rocznik Pedagogiczny, 2021)
The work is devoted to the analysis of the Florian Znaniecki’s idea of the relationships between two systems of values – the social one and the economic one. The presented analysis focuses on the Znaniecki’s theses in the reference to the current market approach to education.